Risk management handbook : a practical guide to managing the multiple dimensions of risk - Hillson, David (London: KoganPage, 2016)
"Risk management is dynamic, with new risks being identified on a continuous basis and risk management techniques adapting to these new challenges. The Risk Management Handbook provides a clear view of the current state of play in the risk management landscape while also looking ahead to the issues in the future. Part One of the book covers the main areas of risk management in business including: enterprise risk management, operational risk, and cyber risk. Chapter authors focus on the distinctive features of their subject and also draw out the overarching themes that apply to all forms of risk management. Part Two introduces and explains emerging trends, from risk-based thinking to communicating uncertainty and ethical risk to risk-based decision-making"--
"Risk management is dynamic, with new risks continually being identified and risk management techniques adapting to new challenges. The Risk Management Handbook gives a clear snapshot of the current state of play in the risk management landscape, and a look ahead to the key emerging issues in the field. Drawing together leading voices from the major risk management application areas - from GRC to supply chain risk, operational risk to cyber risk - this edited collection showcases best practice in each discipline and provides a succinct and coherent picture of the field as a whole. Part One surveys these crucial application areas and provides a broad integrative framework for the differing contexts within which risk management is undertaken. Part Two explores emerging issues and techniques, from risk-based thinking to communicating uncertainty. The Risk Management Handbook offers readers knowledge of current best practice and a cutting-edge insight into new developments within risk management. Whether you are a risk professional wanting to stay abreast of your field, a student seeking a broad and up-to-date introduction to risk, or a business leader wanting to get to grips with the risks that face your business, this book will provide expert guidance"--
Machine generated contents note: About the author 01 Introducing risk -- David Hillson -- What do you do? -- What is risk? -- What is risk management? -- Why does it matter? -- And finally
Includes bibliographical references and index.
Keywords: Risk management; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management; BUSINESS & ECONOMICS / Management